//Exa 4.4 clc; clear; close; disp("The output can be obtained using superposition theorem, as"); disp("Vo=Voa+Vob"); // case (i) when Vb=0; disp("case (i) when Vb=0 the given circuit becomes an inverting amplifier to provide an output as"); disp("Voa=-100Kohm*Va/R1=-2*Va "); disp("It gives R1=50 Kohm"); // case (ii) when Va=0; disp("case (ii) when Va=0 the given circuit becomes an non-inverting amplifier to provide an output as"); disp("Vob=(1+100Kohm/R1)*V1 where V1=R3*Vb/(R2+R3)"); disp("Vob=(1+100Kohm/R1)*V1*(R3*Vb/(R2+R3))=Vb ") disp("Putting R1=R2=50 Kohm, we get R3=25 Kohm");